2012
DOI: 10.1002/car.2218
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Challenges of Training Child Protection Social Workers in Father Engagement

Abstract: It is widely recognised that, in a child protection context, practitioners tend to focus on working with mothers more than fathers. This may undermine risk management and limit the resources available for the care of children. This paper discusses the process of developing and running a training intervention for child protection social workers, designed to improve father engagement (with ‘fathers’ defined inclusively). A short course was provided, consisting of one day of awareness‐raising about the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
(28 reference statements)
1
24
0
2
Order By: Relevance
“…These results are consistent with findings of different local studies which showed similar results in different areas in the Gaza Strip-Palestine (2,3,20,21,25,26,32). As well, different findings worldwide revealed correlation between quality of water, sanitation systems and hygiene behavior with waterborne disease frequency in different countries (22)(23)(24)27). From the other hands, the results demonstrated that the most common age group who suffered from diarrheal diseases among the infected people was children less than 5 years (n=49; 68%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with findings of different local studies which showed similar results in different areas in the Gaza Strip-Palestine (2,3,20,21,25,26,32). As well, different findings worldwide revealed correlation between quality of water, sanitation systems and hygiene behavior with waterborne disease frequency in different countries (22)(23)(24)27). From the other hands, the results demonstrated that the most common age group who suffered from diarrheal diseases among the infected people was children less than 5 years (n=49; 68%).…”
Section: Discussionsupporting
confidence: 91%
“…The global burden of disease and mortality rates could be reduced by about 9.1% and 6.3%, respectively, if rapid success is attained in facilitating access to water, sanitation, and hygiene facilities (18,19). Many studies reported that quality of water, sanitation systems and hygiene behavior are all connected to waterborne disease frequency in the communities (2,3,(20)(21)(22)(23)(24)(25)(26)(27). For instance, promoting the simple and inexpensive hygiene procedure hand washing with soap (HWWS) has proved to be a remarkable effective way to prevent infections in the rural settings of developing countries (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, social work has acknowledged the extent to which this approach can alienate families and training initiatives and co-location schemes have been introduced to develop its practitioners' skills and capacity to engage with abusive fathers (see Maxwell et al 2012;Blacklock and Phillips 2015).…”
Section: Identifying the Key Components Of A 'Whole Family' Interventmentioning
confidence: 99%
“…Therefore, this study addresses this gap in the research by providing descriptive information about the fathers and their personal challenges, their relationships with their children, their relationship with the mother, and with the child welfare system. On the basis of the definitions in previous studies (e.g., Malm et al, ; Maxwell, Scourfield, Holland, Featherstone, & Lee, ; Maxwell, Scourfield, Featherstone, et al, ; Strega et al, ), nonresidential fathers are defined in this study as those who can be birth fathers or social fathers and did not live with children at the time of placement.…”
Section: Introductionmentioning
confidence: 99%